Self-perceived oral health among Brazilian elderly individuals - Martins, Andréa Maria Eleutério de Barros Lima (2010)
OBJECTIVE: To identify factors associated with self-perceived oral health among Brazilian elderly individuals. METHODS: Data from the Projeto SB Brasil (Brazilian Oral Health Project), conducted in 2002-2003, were used. A probabilistic sample of 5,349 elderly individuals, aged between 65 and 74 years, was analyzed, interviewed and subsequently grouped into dentate and edentate individuals. The dependent variable was self-perceived oral health condition, while independent variables were as follows: place of residence, individual characteristics, health-related behavior, objective health conditions and subjective health conditions. Descriptive and hierarchical multiple linear regression analyses were performed. RESULTS: In both groups, self-perceived oral health was considered positive, despite the poor oral health conditions found among the elderly. In the final model, place of residence and individual characteristics contributed little to explain the variability of self-perception. The use of dental services was associated with the outcome in dentate individuals, while objective and subjective conditions were associated in both groups. Among dentate and edentate individuals, R² for the external environment was 0.00; with the inclusion of individual characteristics, 0.05 and 0.02, respectively; with the inclusion of health-related behavior, 0.06 and 0.03, respectively; with the inclusion of objective health conditions, 0.11 and 0.04 respectively; and with the inclusion of subjective health conditions, 0.50 and 0.43, respectively. It was possible to explain 50% of the variability of self-perception in dentate individuals, and 43% in edentate ones. CONCLUSIONS: The main factors associated with self-perceived oral health in both groups were excellent self-perceived appearance, followed by positive self-perceived mastication. The third associated factor was reporting no need for dental treatment in dentate individuals, and self-perceived speech in edentate ones.